The Care of Childhood Cancer Survivors in India: Challenges and Solutions - Maya Prasad; Savita Goswami; Purna A. Kurkure (Indian Journal of Medical and Paediatric Oncology)
Purpose We describe the challenges faced and lessons learnt over three decades of a childhood cancer survivorship program in India.